Effects of COVID-19 stress, proximity, and adverse childhood experiences on healthcare workers’ mental health - Mirhosseini, Tannaz; Guastello, Andrea D.; Dale, Lourdes P.; Sambuco, Nicola; Allen, Brandon R.; Mathews, Carol A. (Frontiers in Psychology, 2023)
Past research has shown that healthcare workers (HCWs) experience high levels of psychological distress during epidemics and pandemics, resulting in cascading effects that have led to chronically understaffed hospitals and healthcare centers. Due to the nature of their responsibilities and workplace stress, HCWs are among vulnerable groups especially during global health crises. During COVID-19 many healthcare workers reported greater symptoms of anxiety, depression, and COVID-19 related worries. Furthermore, adverse childhood experiences increase vulnerability for psychological conditions, especially during pandemics. This study sets out to (1) investigate the moderating effects of adverse childhood experiences on healthcare workers’ COVID-19 related stressors and depression/anxiety symptoms, and (2) investigate the moderating effects of adverse childhood experiences on proximity to the COVID-19 virus and depression/anxiety symptoms. Participants included 438 employed HCWs recruited from academic medical centers and smaller healthcare agencies in northcentral Florida between October to December 2020. Mean age of participants was 38.23 (SD = 11.5) with most of the HCWs being white (72.1%), non-Hispanic (86.8%) and female (82%). Healthcare workers completed several online questionnaires, including the Adverse Childhood Experiences scale, Patient Health Questionnaire, Generalized Anxiety Disorder Scale, a COVID-19 specific worries scale, and a Social Proximity to COVID-19 scale. Healthcare workers experiencing specific COVID-19 worries reported experiencing anxiety and depressive symptoms. A significant positive interaction was seen between childhood adverse experiences globally and COVID-19 worries on anxiety symptoms. A significant positive interaction was observed between childhood maltreatment specifically and COVID-19 worries on depressive symptoms. Additionally, a positive interaction effect was seen between childhood adverse experiences and COVID-19 social proximity for both depression symptoms and anxiety symptoms. Findings from the present study indicate that adverse childhood experiences strengthen the relationship between COVID-19 worry/proximity and negative psychological symptoms. Vulnerable populations such as individuals who have experienced ACEs could benefit from targeted and specific interventions to cope with the collective trauma experienced globally due to COVID-19. As COVID-19 becomes endemic, hospital leadership and authorities should continue addressing COVID-19 worries and HCWs’ psychological symptoms through mental health support and organizational interventions.